HYBRID PHOTOVOLTAIC-ASSISTED HIDROGEN PRODUCTION USING ALKALINE ELECTROLYSIS METHOD - Eka Rachmatillah Ahmad, Rizky
Hydrogen production through electrolysis using solar energy can be an effective method to overcome environmental issue due to excessive use of fossil fuels but is still constrained by the instability of solar radiation. The use of other electricity sources such as conventional electricity as a complement can stabilize the energy supply for the hydrogen production. This study aims to examine the configuration of water electrolysis system and optimum operating conditions, and analyze the performance of hydrogen production systems using photovoltaic and conventional electricity as a source of electricity. Water electrolysis was carried out using KOH 3M electrolyte solution in a double chamber electrolysis cell. The type of electrode varies between nickel and SS (stainless steel) with variations in the shape of spiral wire and mesh. Electrolyte conditions were compared at several flow rates 0; 3.72; and 10 mL/s. Electrolysis of water using solar energy is carried out at 09.00 to 16.00 with 100 Wp photovoltaic capacity, while photovoltaic used for hybrid energy systems with a capacity of 1000 Wp. Electrolysis performance is analyzed by measuring the volume of hydrogen, the density of energy needed, and electrolysis current efficiency. The results showed that the optimum conditions for electrolysis of water in 3 M KOH solution using a conventional power source at a working voltage of 2.6 V were achieved with nickel mesh electrodes and an electrolyte flow rate of 3.72 mL/s, capable of producing 140 mL of hydrogen with a current efficiency of 70.5% and electrical energy needs 25.9 kJ/L. Water electrolysis using photovoltaic produces 5.625 L of hydrogen with stable irradiation between 09:00 - 15:00 hours with a voltage of 1.98 - 15.0 V, currents from 0.05 to 3.13 A with 71.8% efficiency. The use of hybrid systems can stabilize the production of hydrogen for electrolysis at a voltage of 15 V for 7 hours, using PLN electrical energy of 581.08 kJ (saving 81.64%), producing 6.6 L hydrogen with 60.69% current efficiency and 38.9% electricity conversion efficiency.